BEHAVIOR MODIFICATION DEVICE, BEHAVIOR MODIFICATION METHOD, AND BEHAVIOR MODIFICATION SYSTEM - IBATA, Koji; AWANO, Tomoharu; WATANABE, Misato; HIRANO, Jin (2023)
A behavior modification device (2) is configured so as to comprise: a sensing information acquisition unit (11) that acquires sensing information from a sensor (1) for observing a monitor area; and a behavior identification unit (12) that identifies, on the basis of the sensing information acquired by the sensing information acquisition unit (11), the behavior of a creature to be intimidated that is present within the monitor area. The behavior modification device (2) further comprises: a stimulus parameter determination unit (13) that determines, in accordance with the behavior identified by the behavior identification unit (12), a parameter pertaining to a stimulus to be given to the creature; and a stimulus data generation unit (14) that generates, in accordance with the parameter determined by the stimulus parameter determination unit (13), stimulus data for generating the stimulus, and outputs the stimulus data to an actuator (3) for stimulus generation. Le dispositif de modification de comportement (2) selon l'invention est configuré de façon à comprendre : une unité d'acquisition d'informations de détection (11), qui acquiert des informations de détection provenant d'un capteur (1) afin d'observer une zone de surveillance ; et une unité d'identification de comportement (12) qui identifie, sur la base des informations de détection acquises par l'unité d'acquisition d'informations de détection (11), le comportement d'un animal devant être intimidé et qui est présent à l'intérieur de la zone de surveillance. Le dispositif de modification de comportement (2) comprend en outre : une unité de détermination de paramètre de stimulus (13) qui détermine, selon le comportement identifié par l'unité d'identification de comportement (12), un paramètre relatif à un stimulus devant être donné à l'animal ; et une unité de génération de données de stimulus (14) qui génère, selon le paramètre déterminé par l'unité de détermination de paramètre de stimulus (13), des données de stimulus pour générer le stimulus, et fournit les données de stimulus à un actionneur (3) afin de générer un stimulus. 監視エリアを観測するセンサ（１）のセンシング情報を取得するセンシング情報取得部（１１）と、センシング情報取得部（１１）により取得されたセンシング情報に基づいて、監視エリア内に存在している威嚇対象の生物の行動を特定する行動特定部（１２）とを備えるように、行動変容装置（２）を構成した。また、行動変容装置（２）は、行動特定部（１２）により特定された行動に応じて、生物に与える刺激のパラメータを決定する刺激パラメータ決定部（１３）と、刺激パラメータ決定部（１３）により決定されたパラメータに従って、刺激を生成するための刺激データを生成し、刺激データを刺激生成用のアクチュエータ（３）に出力する刺激データ生成部（１４）とを備えている。